Ascent, descent, nullity and defect of linear operators - Nichol, John Robert (Department of Mathematics and Applied Mathematics, 2016)
This thesis is intended to be a survey of nullity and defect of linear operators on the one hand, and ascent and descent on the other, and the relationships between these concepts. These quantities are of considerable use in the discussion of linear operators, e.g. compact operators.